Effect of the Covid-19 Pandemic on Vaccination Coverage of the Population Under 2 Years of Age, Ibarra- Ecuador - Rivas-Condo, Jackson Robert; Solís-Castro, María Edith; Torres-Baltán, Carla Katherine; González-Quintanilla, Nancy Patricia; Espinales-Párraga, Karen Andrea (Journal of Posthumanism, 2025)
This study analyzes the impact of the Coronavirus (SARS-CoV-2) pandemic on the coverage of the regular vaccination schedule in children under two years of age in the canton of Ibarra, Ecuador, between 2018 and 2021.The research design is quantitative, descriptive, and cross-sectional, with data obtained from administrative records and surveys directed at vaccination program managers.The findings reveal a substantial decline in vaccination coverage during the pandemic, with statistically significant differences observed between the periods 2018-2020, 2019-2020, 2018-2021, 2019-2021, and 2020-2021 (p < 0.001). The coverage among children under one year of age decreased from 176.1% in 2018 to 134.9% in 2021, while among girls, it dropped from 160.5% to 121.1%, indicating a downward trend also among those over one year of age. A statistically significant disparity was observed between urban and rural areas, with a decline more pronounced in urban regions during the 2020-2021 period (p = 0.048). Furthermore, three socioeconomic quintiles (1, 2, and 4) exhibited coverage rates below 50% during the specified period. The primary barriers identified included reassignment of health personnel to the care of patients with severe acute respiratory syndrome (88.8%), mobility restrictions (77%), and vaccine shortages (66.6%).Consequently, the pandemic exerted a detrimental influenc e on childhood vaccination coverage, thereby heightening the risk of immunopreventable diseases and underscoring the imperative for the formulation of strategies to ensure the sustainability of immunization programs in emergency contexts.